Analisis Harga Saham dengan Pendekatan Ekonometrika (Studi di Bursa Efek Indonesia) - Atim Djazuli (Jurnal Aplikasi Manajemen, 2012)
This research aimed to test and analyze the influence of Return on Investment, Current Ratio, Dividend, Gross Domestic Product, Currency, and Interest Rate to stock price altogether. This research used econometrics approach by implementing multiple regression analysis method. The research population is all companies listed in Indonesian Stock Exchange in the period of 2001-2007 out of which 52 companies were selected as samples to be observed within 7 (seven) years term resulting in as many as 364 observations. The results of this research indicate that the variables having an effect on stock price were Return on Investment, Current Ratio and Dividend. Finally the variables which had insignificant influences stock price were the variable of Gross Domestic Product, Currency and interest rate.Keywords: Return on Investment, Current Ratio, Dividend, Gross Domestic Product, Currency, Interest Rate and stock price.